2017
DOI: 10.1117/12.2262452
|View full text |Cite
|
Sign up to set email alerts
|

Review of colored conformal symbology in head-worn displays

Abstract: The usage of conformal symbology in color head-worn displays (HWDs) opens up a range of new possibilities on modern flight decks. The capability of color augmentation seems especially useful for low flights in degraded visual environments. Helicopter flights in these conditions, including brownout by swirling dust or sand particles, can often lead to spatial disorientation (SD) and result in a significant amount of controlled flight into terrain (CFIT). While first generation color-capable conformal displays a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Only recently, there has been a growing number of publications addressing this topic. [1][2][3][4][5][6] For instance, Havig et al 7 presented subjects red, green and yellow symbology in increasing luminance contrasts on different natural background colors to find recognition thresholds. The results showed that especially yellow was detected incorrectly but also that yellow was confused with green.…”
Section: Literature Research On Hmd Color Codingmentioning
confidence: 99%
“…Only recently, there has been a growing number of publications addressing this topic. [1][2][3][4][5][6] For instance, Havig et al 7 presented subjects red, green and yellow symbology in increasing luminance contrasts on different natural background colors to find recognition thresholds. The results showed that especially yellow was detected incorrectly but also that yellow was confused with green.…”
Section: Literature Research On Hmd Color Codingmentioning
confidence: 99%